2009
DOI: 10.3109/09638280903183829
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative study of principles pertaining to lifestyle and pressure ulcer risk in adults with spinal cord injury

Abstract: Principles pertaining to the relationship between in-context lifestyle and pressure ulcer risk underscore previous quantitative findings, but also lead to new understandings of how risk unfolds in everyday life situations. Pressure ulcer prevention for community-dwelling adults with SCI can potentially be enhanced by incorporating principles, such as the decay of prevention behaviors or lifestyle trade-off, that highlight special patterns indicative of elevated risk. The identified principles can be used to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 31 publications
(34 reference statements)
4
44
0
Order By: Relevance
“…Russell (2008), in her analysis of tagging, illustrated the complex interplay of health-promoting (e.g., problem solving, social participation) and healthcompromising (e.g., physical danger, threat of arrest and prosecution) elements of this particular occupation. The study also mirrors a finding by Jackson et al (2010), who, in their analysis of factors contributing to pressure ulcer risk in adults with spinal cord injury, found that when people developed a pressure ulcer, they faced the difficult decision of whether to remain engaged in their usual patterns of activities or submit to an extended period of bed rest to heal. Because both options had health-promoting and health-compromising elements, the decision required a careful analysis of potential risks and benefits.…”
Section: Discussionsupporting
confidence: 79%
“…Russell (2008), in her analysis of tagging, illustrated the complex interplay of health-promoting (e.g., problem solving, social participation) and healthcompromising (e.g., physical danger, threat of arrest and prosecution) elements of this particular occupation. The study also mirrors a finding by Jackson et al (2010), who, in their analysis of factors contributing to pressure ulcer risk in adults with spinal cord injury, found that when people developed a pressure ulcer, they faced the difficult decision of whether to remain engaged in their usual patterns of activities or submit to an extended period of bed rest to heal. Because both options had health-promoting and health-compromising elements, the decision required a careful analysis of potential risks and benefits.…”
Section: Discussionsupporting
confidence: 79%
“…Decisions in daily activities, decay in adherence to prevention behaviors, lack of situational awareness, motivation, and access to needed services and supports are among the key principles pertaining to lifestyle that could increase the risk of developing PUs [11]. For example, skipping scheduled prevention activities to attend to work is commonly reported [11].…”
Section: Lifestyle and Psychosocial Factorsmentioning
confidence: 99%
“…These studies examining the sequence of events leading to the development of PUs demonstrate that unexpected events (e.g., lengthy flight delay, change in care personnel) disrupt established prevention routines [26]. Decisions in daily activities, decay in adherence to prevention behaviors, lack of situational awareness, motivation, and access to needed services and supports are among the key principles pertaining to lifestyle that could increase the risk of developing PUs [11]. For example, skipping scheduled prevention activities to attend to work is commonly reported [11].…”
Section: Lifestyle and Psychosocial Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Pressure ulcers are secondary complications to SCI that lead to lower quality of life and are expensive to treat. [1][2][3] The least expensive and most difficult management of pressure ulcers is prevention. 4 Persons with SCI are prone to develop high seating pressure because of spine deformities, muscle imbalance and deteriorated perception.…”
Section: Introductionmentioning
confidence: 99%